The study of digital tools and business negotiations in cross-cultural communication ( based on Uzbek and English languages) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This thesis explores the pivotal role of digital tools and business negotiations within the framework of cross-cultural communication, specifically focusing on the interactions between Uzbek and English speakers. As globalization continues to reshape business landscapes, understanding how digital tools—such as email, video conferencing, and social media—facilitate or hinder effective communication across cultural boundaries has become increasingly vital. By examining the unique communication styles and strategies utilized in business negotiations, this research aims to identify the influence of cultural differences and linguistic nuances on negotiation outcomes. The findings will provide actionable insights for improving international business relations and fostering more effective cross-cultural communication.